Inovasi Produk dan Strategi Pemasaran Kue Pukis Mini sebagai Peluang Usaha Kuliner Kreatif Berbasis UMKM - Resti Ningrum; Wulan Rizki Ramdani; Ita Purnama (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze product innovation and marketing strategies of mini pukis cake as a development model of creative culinary businesses based on Micro, Small, and Medium Enterprises (MSMEs). The research employs a descriptive qualitative approach using observation, interviews, and documentation techniques involving an MSME practitioner in Bima City, West Nusa Tenggara. The results indicate that product innovation is implemented through mini-sized portions, diverse topping variations, and appealing packaging that significantly enhance consumer interest. Marketing strategies rely on social media platforms such as Instagram and WhatsApp, as well as word-of-mouth promotion. While innovation and marketing efforts have shown positive outcomes, the business faces challenges in financial management, particularly in cash recording and cost of goods sold (COGS) calculation. Business mentoring through financial literacy training and branding strategy support has proven effective in improving operational efficiency. The study concludes that integrating creative product innovation with digital marketing is an effective strategy to grow local culinary businesses within the MSME sector. Keywords: product innovation, marketing strategy, MSMEs, mini pukis, creative culinary business